Shakespeare in Atlantic Canada During the Nineteenth Century - Smith, Mary Elizabeth (Theatre Research in Canada / Recherches théâtrales au Canada, 1982)
While performances of Shakespeare were by no means frequent in Halifax and Saint John, except during the twenty year period 1857-1877 in the latter city, they were nevertheless an important part of the overall theatrical scene. This article describes the actors and companies who presented adaptations of Shakespearean plays in these two cities and examines audience reaction in the light of newspaper reviews. Quoique des représentations des pièces de Shakespeare ne furent jamais fréquentes à Halifax et à Saint John, sauf entre 1857 et 1877 dans cette dernière ville, elles jouèrent néanmoins un rôle important dans le domaine du théâtre. Cet article décrit les acteurs et les troupes qui présentèrent des adaptions de pièces de Shakespeare dans ces deux villes et examine la réaction du public de par les revues des journaux.